Withania somnifera extract reduces the invasiveness of MDA-MB-231 breast cancer and inhibits cytokines associated with metastasis - Khazal, Kamel F. (J Cancer Metastasis Treat, 2015)
AIM: The aim was to examine the anti-proliferative effect of a Withania somnifera (WS) root extract in cell cultures and nude mouse xenografts of breast cancer cell line MDA-MB-231. METHODS: WS root extract was used to treat tumor cells at concentrations up to 100 µg and for nude mouse experiments, the mice received daily WS at 300 mg/kg by oral gavage for 8 weeks. RESULTS: The WS extract reduced viability of MDA-MB-231 cells by 75% and 88% after exposure of the cells to 50 and 100 µg/mL, respectively, compared to vehicle-treated controls. WS extract caused a dose-dependent increase in the percentage of cells in the sub-G1 phase compared to untreated controls by 6% and 10% after exposure to 25 and 50 µg/mL WS extract, respectively. WS extract also inhibited proliferation of xenografted MDA-MB-231 cells. The WS extract caused reductions in xenograft size by 60% compared to the untreated control after 8 weeks of treatment. Six of ten mice in the control group showed tumor metastasis to the lung, whereas there was none in the mice treated with the WS extract. At the gene level, WS caused a 75% reduction in chemokine CCL2 expression (P < 0.05) in the xenografted tumors of the treated mice. CONCLUSION: WS root extract inhibited proliferation of breast cancer cells in vitro and in vivo and significantly reduced expression of the cytokine, CCL2. These results warrant further studies to assess the underlying molecular mechanism of the anti-tumor activity of the WS extract in breast cancer.